Sulawesi Onthophagus: seven new species in select groups (Coleoptera: Scarabaeidae: Scarabaeinae) - Krikken, J.; Huijbregts, J. (Zootaxa, 2017)
Eleven species in five small operational groups of the scarab genus Onthophagus Latreille, 1802 (Coleoptera: Scarabaeidae: Scarabaeinae) are treated, all from the Indonesian island of Sulawesi and nearby smaller islands. These groups are defined, and their species are keyed, described, and illustrated, including the following seven new species: Onthophagus bisscrutator (O. scrutator group); O. bongkudai (O. holosericus group); O. sopu (O. manguliensis group); O. hollowayi, O. seseba, and O. annulopunctatus (O. seseba group); and O. begoniophilus (O. deflexicollis group). Lectotypes are designated for Onthophagus scrutator Harold, 1877 and O. holosericus Harold, 1877.